Rage or rationality: Exposure to Internet censorship and the impact on individual information behaviors in China. Issue 4 (19th June 2022) - Zhang, Langcheng; Tandoc, Edson C.; Han, Sukhee
Abstract: Studies showed that personal experience with censorship can trigger psychological and behavioral resistance in individual users. However, it is still unclear whether this impact goes beyond those who are censored and to those who witness or are made aware of censorship at work. Through a survey of 481 college students in China, this study examined the relationships between censorship exposure, emotions, and information behaviors on sensitive issues online. The result shows that more exposure, though with a modest effect, predicts higher levels of anger and acquisition and production of information on censored topics. Anger itself is also a predictor of higher information acquisition and production, while fear is only negatively related to information production. Implications are made for future research and Internet policy evaluation. 摘要: 研究表明，个人在审查制度方面的经历会引发个体用户的心理抵制和行为抵制。不过，尚不清晰的是，这种影响是否不仅波及那些被审查的个体，还波及那些目睹或在工作中被告知审查制度的群体。通过对中国481 名大学生进行调研，本研究分析了审查暴露（censorship exposure）、情感、以及网络敏感问题上的信息行为之间的关系。结果表明，虽然影响较小，但更多的审查暴露预示着更高水平的愤怒以及对审查主题信息的获取和生产。愤怒本身也预示更多的信息获取和生产，而恐惧只与信息生产呈负相关。本研究为未来研究和互联网政策评价提供了一系列意义。 Resumen: Los estudios demostraron que la experiencia personal con la censura puede desencadenar resistencia psicológica y conductual en los usuarios individuales. Sin embargo, aún no está claro si este impacto va más allá de quienes son censurados y de quienes presencian o son conscientes de la censura en el trabajo. A través de una encuesta de 481 estudiantes universitarios en China, este estudio examinó las relaciones entre la exposición a la censura, las emociones y los comportamientos de información sobre temas delicados en línea. El resultado muestra que una mayor exposición, aunque con un efecto modesto, predice mayores niveles de ira y adquisición y producción de información sobre temas censurados. La ira en sí misma también es un predictor de una mayor adquisición y producción de información, mientras que el miedo solo se relaciona negativamente con la producción de información. Se hacen implicaciones para futuras investigaciones y evaluaciones de políticas de Internet.